High performance epoxy composites prepared using recycled short carbon fiber with enhanced dispersibility and interfacial bonding through polydopamine surface-modification. (15th July 2020) - Huan, Xianhua; Shi, Ke; Yan, Jiqiang; Lin, Song; Li, Yanjie; Jia, Xiaolong; Yang, Xiaoping
Abstract: The critical issue and challenge in reusing recycled carbon fiber (rCF) was to fully exerting its outstanding properties via an efficient and environmental-friendly way. In this study, the strengthening effects of polydopamine surface-modified recycled short CF (pDop-rSCF) on mechanical, thermo-mechanical, electrical and electromagnetic properties of epoxy (EP)-based composites were systematically evaluated. The dispersibility of pDop-rSCF in suspension used for fabricating nonwoven mat was quantitatively characterized with crowding factor N, dispersion coefficient β and fractal dimension D. Significant enhancements were achieved in tensile and flexural properties, interlaminar shear strength, storage modulus and electromagnetic interference shielding capability of EP composites reinforced with pDop-rSCF nonwoven mat, which was primarily ascribed to chemically strengthened interfacial bonding between pDop-rSCF and EP matrix and the increased connectivity among pDop-rSCFs with excellent dispersion.